Análise de cenários de mudanças no clima e de diferentes narrativas socioeconômicas sobre alteraç\~oes no uso do solo e na agricultura - Wanderson Santos Costa; Heloísa Musetti Ruivo; Aline Cristina Soterroni; Fernando Manuel Ramos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– This paper presents the results of simulations of agricultural and forestry production in Brazil, using the GLOBIOM-Brazil Model, of the effects of climate change in relation to the scenario without climate change and also of different scenarios of global socioeconomic projections. The simulations of the effects of climate change consider the loss of agricultural productivity due to the occurrence of extreme degree days, particularly damaging during grain growth periods. The general results of this scenario compared to the baseline, without climate change, is that Brazilian grain production tends to be maintained, but using a considerably larger area. There is also a shift in the concentration of agricultural production towards the south of the country. Pasture areas would be the main sources of expansion of the agricultural area. In the scenarios of different socioeconomic projections, based on the Shared Socioeconomic Pathways (O'Neill et al. 2017), production and area demanded follow the demand profile of each scenario. The scenario of lower population growth and a diet less based on animal protein requires less production and area for livestock farming and, to a lesser extent, for agriculture. In the scenarios of higher population growth, and even with different income level and distribution profiles, the projections for agricultural production and area allocated to these activities follow the demand patterns. As for forest cover, the scenario with the largest projected area is that of lower population growth and a diet less based on animal protein, which consequently generates less pressure to open new areas for livestock farming.
Keywords: R11; R12; Q1; 330; Globiom-Brazil; land use model; agricultural